2000
DOI: 10.1136/ard.59.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and monitoring of central nervous system involvement in systemic lupus erythematosus: value of F-18 fluorodeoxyglucose PET

Abstract: Objective-To investigate prospectively abnormalities of brain glucose utilisation in relation to major or minor neuropsychiatric symptoms in systemic lupus erythematosus (SLE). Methods-Positron emission tomography (PET) using F-18-labelled fluorodeoxyglucose was performed in 28 patients with SLE. Patients were classified as having severe neuropsychiatric manifestations (seizures, focal neurological deficits, acute confusional states, mood disorders) (n=12), or mild neuropsychiatric manifestations (headache, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
2
10

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 49 publications
(47 reference statements)
0
75
2
10
Order By: Relevance
“…For example, several studies reported either glucose hypometabolism or hypoperfusion in the temporal, parietal, and frontal lobes (Stoppe et al 1990;Lin et al 1997;Kao et al 1999). Weiner et al (2000) found hypometabolism in similar areas including the frontal lobes, but little involvement of temporal areas. Using high resolution instrumentation with SPECT, Kao et al (1999) detected deficits in deeper brain structures such as the basal ganglia.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
“…For example, several studies reported either glucose hypometabolism or hypoperfusion in the temporal, parietal, and frontal lobes (Stoppe et al 1990;Lin et al 1997;Kao et al 1999). Weiner et al (2000) found hypometabolism in similar areas including the frontal lobes, but little involvement of temporal areas. Using high resolution instrumentation with SPECT, Kao et al (1999) detected deficits in deeper brain structures such as the basal ganglia.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
“…Paiva et al [10] found that 10% of lupus patients without CNS symptoms had abnormal visual evoked potential (VEP), while 56% of those had CNS involvement. Waterloo et al [11] found abnormal EEG in 19% of patients with SLE, while magnetic resonance imaging was abnormal in 11 of 22 patients with neuropsychiatric symptoms and in 1 of 4 patients without symptoms [12].…”
Section: Introductionmentioning
confidence: 99%
“…Im Gegensatz zur eingeschränkten Aussagekraft einer einzelnen MRT-Untersuchung zeigt sich, dass in MRT-Verlaufsuntersuchungen das Ansprechen auf eine Therapie dokumentiert werden kann [100]. [16], Kozora et al [56], Sabbadini et al [91], Sibbitt et al [95], Weiner et al [110]). …”
Section: Magnetresonanztomographie (Mrt)unclassified
“…Bei Patienten mit APS finden sich MRT-Veränderungen in bis zu 75% der Fälle [45,79,92]. Wir fanden MRT-Auffälligkeiten bei 67% der Patienten mit schwerer neuropsychiatrischer Symptomatik und bei 30% der Patienten mit milden klinischen Symptomen [110]. Patienten zeigen sich in Abhängigkeit von der Erkrankungsdauer im MRT Auffälligkeiten in 16-52% vor allem in Form von kortikaler Atrophie und Marklagerläsionen [16,35,48,91,95,100].…”
Section: Neuropsychiatric Involvement In Systemic Lupus Erythematosusunclassified